(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
In the evolving landscape of English language teaching, the integration of pragmatic, strategic, and sociolinguistic competences into curricula is crucial for developing proficient communicators in a globalized world. Emphasizing these competences in teaching methodologies can significantly enhance the communicative competence of English learners, preparing them better for the challenges of global communication. This paper describes the features that equip learners not only with linguistic proficiency but also with the critical socio-cultural, pragmatic and strategic skills needed in real-world interactions